Product Market Competition and Voluntary Corporate Social Responsibility Disclosures† - Ryou, Ji Woo; Tsang, Albert; Wang, Kun Tracy (Contemporary Accounting Research, 2022)
ABSTRACT This study examines whether and how firms' voluntary forward‐looking nonfinancial disclosure, specifically their corporate social responsibility (CSR) disclosure, is associated with the intensity of product market competition (PMC). Despite the importance of the proprietary cost argument in explaining corporate disclosure incentives, there is little empirical evidence of the relationship between firms' proprietary cost concerns and their voluntary nonfinancial disclosure decisions. Using a reduction in industry‐level import tariffs as an exogenous shock to competition intensity, we find that the likelihood, frequency, and length of stand‐alone CSR reports decrease in response to heightened PMC. We also find that higher PMC intensity is associated with a reduced likelihood of CSR disclosure with external assurance, CSR disclosure in accordance with the Global Reporting Initiative guidelines, and CSR disclosure integrated with financial statements. Our results are robust to multiple alternative measures of PMC—namely, the level of nonprice competition, product similarity, and managers' perceptions of competition. Further analysis suggests that firms facing intense competition tend to commit more resources to advertising activities after reducing their CSR disclosure, presumably to mitigate the effect of this reduction. Overall, our findings suggest that proprietary cost concerns reduce firms' incentive to report their competition‐sensitive CSR activities.